The wrath of Mulgarath - DiTerlizzi, Tony; Black, Holly (New York Simon and Schuster Books for Young Readers, 2004)
Three ordinary kids, Jared, Simon, and Mallory Grace, have entered another world without leaving this one!
In which: The world is turned upside down--In which: An old friend returns--In which: Jared finds out things he doesn't want to know--In which: Everything goes into the fire--In which: They find the meaning of "here there be dragons"--In which: All hell breaks loose--In which:The story of the grace children comes to its conclusion--About Tony DiTerlizzi and Holly Black.
Keywords: Children -- Juvenile fiction; Supernatural -- Juvenile fiction